2021
DOI: 10.1192/bjb.2021.7
|View full text |Cite
|
Sign up to set email alerts
|

Soaring seas, forest fires and deadly drought: climate change conspiracies and mental health

Abstract: Summary There is scientific consensus that anthropogenic climate change is real and that it provides an existential threat to humanity and the planet. In this article, we focus on climate change conspiracy theories and the impact of such beliefs on mental health. We discuss the psychiatric disorders that might be relevant to conspiracy belief endorsement and we present the underlying psychological mechanisms. We note that there is little to no literature to associate beliefs about climate change with seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…These findings may have important social implications. Research has now clearly shown that BWSSE are not ‘fringe’, but instead are common [ [10] , [11] , [12] , [13] ]. In the COVID-19 health pandemic, surveys from the UK, Europe, and North America suggested that 30–40% of the population endorsed, to some degree, at least one COVID-related conspiracy theory belief [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings may have important social implications. Research has now clearly shown that BWSSE are not ‘fringe’, but instead are common [ [10] , [11] , [12] , [13] ]. In the COVID-19 health pandemic, surveys from the UK, Europe, and North America suggested that 30–40% of the population endorsed, to some degree, at least one COVID-related conspiracy theory belief [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…BWSSEs were first studied under the concepts of schizotypy, psychosis-proneness, or delusional ideation, conceptualized to occur on a continuum with clinically significant delusions in schizophrenia and psychosis [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] ]. However, given the recent coronavirus disease (COVID-19) pandemic and related political events, BWSSE have captured the attention of the media and the general public, and it has become clear that BWSSE are much more widespread than previously thought [ [10] , [11] , [12] , [13] ], extending well beyond parallels for psychotic delusions. In particular, endorsement of conspiracy theories can lead to social and health-related consequences, such as increased risk of viral infection with refusal of vaccinations (Oleksy et al, 2021; Ripp & Röer, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation